Penanaman Karakter Peduli Lingkungan Pada Siswa di SD Negeri Sukamulya I Melalui Program KURASSAKI - Siti Rufaidah, Annisa; Suparno; Jamaludin, Ujang (JURNAL PENDIDIKAN DASAR NUSANTARA, 2020)
Abstract: This study aims to determine the inculcation of environmental care character among students at SDN Sukamulya I through the Kurassaki program. This study uses descriptive qualitative research methods, the resource persons in this study are the principal, teachers, and students. Data collection techniques used were interviews, observation, and documentation, which were then analyzed using the Miles and Huberman models. The results of this study indicate that: 1) Planting environmental care characters in students at SDN Sukamulya I through the Kurassaki program is carried out through three stages: the planning stage, the implementation phase, and the evaluation stage 2) Supporting and inhibiting factors in the implementation of the Kurassaki program, supporting factors of teacher namely the existence of training from the Kurassaki program supervisor who was followed by the teacher to optimize the implementation of the program, from students the characteristics of elementary school children who are still imitative make it easy for students to be directed and participate in the implementation of the program, from facilities and infrastructure that is the availability of supporting facilities and infrastructure. Barriers from students are forgetting to bring food and drink containers, as well as lack of responsibility in maintaining cleaning equipment, from facilities and infrastructure, there are damaged and missing cleaning equipment.